Teachers’ Perceptions towards English Language Teaching Pedagogy in Secondary Schools of Nepal (KMC Journal, 2024)
Recently research on English language teaching pedagogy has been receiving increased attention throughout the world, with a primary focus on classroom teaching strategies. This qualitative research study aims to explore the narratives of English language teachers about the use of English language teaching pedagogy in secondary schools in Nepal. The participants purposively selected for this study were four English language teachers teaching at the secondary level in public schools of Kanchanpur district. The researcher used narrative inquiry as a research method in which interview protocols with open-ended questions were employed as research tools to obtain information. The findings of the study showed that secondary English teachers have been shifting their classroom pedagogy from traditional teacher-centred approaches to modern innovative student-centred approaches. The study further revealed that teachers keep the knowledge of both teacher-centred and student-centred methods and techniques but practise them in the classrooms in their ways due to the limitations of prescribed methods. The study also revealed students’ level of English as the main barrier to their learning progress. The implication of the study is that the teachers should create more learning opportunities and environments inside and outside the classroom to increase students’ maximum time engagement in English learning-based activities that provide them with more exposure to English and enhances their learning.